Feasting on fish. Specialized function of pre-colonial pottery of the Cerritos mound builders of southern Brazil - Marjolein Admiraal; André C. Colonese; Rafael Guedes Milheira; Alice Di Muro; Helen Marie Talbot; Alexandre Lucquin; Oliver E. Craig (PLoS ONE, 2025)
Some of the oldest coastal pottery in South America is found in the Pampas region of southern Brazil, Uruguay and Argentina. In the region’s extensive estuarine systems pre-colonial indigenous groups built earthen mounds, known as Cerritos, from ca. 4700 BP. The Cerritos have multifunctional purposes, and while pottery was widely used, its role in the economic or ritual life of the mound builders remains uncertain. Intriguingly, molecular and isotopic characterization of food residues from Cerritos ceramics shows that vessels were used for either cooking estuarine fish, or plant products. Microbial-derived lipids were predominantly associated with the latter, suggesting that plants were fermented, presumably to make alcoholic beverages. We suggest that dispersed communities were drawn to the mounds seasonally to exploit and celebrate the return of migrating fish. This finding is supported by the diversity of stable isotope values of human remains recovered from Cerritos and sheds new light on the lifeways of these pre-colonial groups.